Moral injury among Akan women: Lessons for culturally sensitive child welfare interventions. (March 2020) - Haight, Wendy; Korang-Okrah, Rose; Black, James E.; Gibson, Priscilla; Nashandi, Ndilimeke J.C.
Highlights: Moral injury is of increased concern to child welfare professionals and scholars. Akan widows and their children are an exemplary case study to consider the cultural shaping of moral injury and healing. Participants described morally injurious events and responses consistent with western literature. Women's vulnerability to morally injurious events was enhanced due to culturally-based practices. The Akan cultural context also provided resources for healing. Abstract: The experience of moral injury is of increased concern to child welfare professionals. This ethnographic study uses Akan (Ghanaian) women who are widowed and their children as an exemplary case study to consider the cultural shaping of moral injury, and implications for culturally-sensitive child welfare practice. We conducted in-depth, semi-structured, audio-recorded interviews. Twenty-one widows, 14 religious professionals providing services to widows, and one secular professional participated. Participants identified some morally injurious events and responses consistent with the Western literature, for example, events involving betrayal of widows and their children were associated with feelings of intense sadness, rage, and spiritual or existential crises. Other events and responses were culturally nuanced. Women's vulnerability to morally injurious events was enhanced due to culturally-based gender roles, widowhood rituals and customary laws involving inheritance. In addition, these events were interpreted and experienced through Akan spirituality in which the self is comprised of the soul, spirit and body; and moral injury, or "soul killing, " involves the dissolution of this trinity and embitterment of the soul. The Akan cultural context also provided resources for healing. Akan women who were widowed articulated the empowerment and restoration they felt from coming together in a community both to address a common challenge (supporting themselves and their children financially), and to receive spiritual and psychosocial support from peers and professionals. This paper provides both a conceptual framework for the empirical examination of the cultural shaping of moral injury, and empirical data within a non-Western cultural context.